PEMBUATAN CENDERAMATA KHAS KARIMUNJAWA BERBASIS POTENSI LOKAL - Raden Ernasthan Budi Prasetyo; Aries Budi Marwanto; Satriana Didiek Isnanta (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2022)
ABSTRACT Karimunjawa is a National Park area that is famous for its beautiful natural potential and full of charm, besides that Karimunjawa also has a lot of potential - priceless natural wealth potential, namely the cultural diversity that exists in people's lives, which is inhabited by various ethnic groups living in the area. living permanently hundreds of years ago created cultural diversity that grew and developed, making Karimunjawa the embodiment of diversity in Indonesia who live in peace and coexistence in Karimunjawa. As a result, the process of cultural acculturation in Karimunjawa cannot develop and it isn't easy to produce unique cultural products in Karimunjawa. Given this, the PKM implementers assist in making Karimunjawa products and train the community on the batik-making process using eco print, stamp, and natural dye techniques. The method used is Participatory Rural Appraisal (PRA) which emphasizes community involvement in all activities ranging from planning, implementing, and evaluating program activities and Community development models, namely an approach that involves the community directly as the subject and object of implementing community service activities. The output of this PKM is a product. and KI.